Branch duct intraductal papillary mucinous neoplasm - contra resection - Brunner, Michaela; Kersting, S.; Grützmann, Robert; Weber, Georg (Chirurg, 2017)
Due to improvements in imaging modalities the diagnosis of branch duct intraductal papillary mucinous neoplasms (BD-IPMN) has been significantly increased in recent years. A BD-IPMN is frequently diagnosed as an incidental finding in asymptomatic patients. The optimal management of BD-IPMN is the subject of controversial discussions. Numerous studies have shown that an individualized therapeutic strategy with a follow-up observation of most BD-IPMNs is feasible and safe, considering age, comorbidities and patient preference. An accurate evaluation of BD-IPMN with a detailed anamnesis, high-resolution imaging techniques and endoscopic ultrasound is necessary. Symptomatic patients as well as patients with so-called high-risk stigmata should undergo resection. Asymptomatic patients with so-called worrisome features can either undergo surveillance or surgical resection, taking age and comorbidities into account. For BD-IPMN patients without high-risk stigmata and worrisome features and showing no symptoms, surveillance of the pancreatic lesion is the preferred approach. The high prevalence of BD-IPMN, limitations in differential diagnostics, an overestimation of the risk of malignancy due to an overrepresentation of symptomatic and suspected BD-IPMN in resected cohorts, an overestimated role of BD-IPMN as precursor lesions for pancreatic carcinoma and evidence of the safety of follow-up surveillance, underline the enormous importance of surveillance. Based on this and considering the background of a notable mortality and morbidity of pancreatic surgery, aggressive management with prophylactic surgical resection is not justified for all BD-IPMN, in particular for low-risk lesions.
EVALuna2:15288